Human striatum is differentially activated by delayed, omitted, and immediate registering feedback - Kohrs, Christin; Angenstein, Nicole; Scheich, Henning; Brechmann, André (Frontiers in Human Neuroscience, 2012)
The temporal contingency of feedback during conversations is an essential requirement of a successful dialog. In the current study, we investigated the effects of delayed and omitted registering feedback on fMRI activation and compared both unexpected conditions to immediate feedback. In the majority of trials of an auditory task, participants received an immediate visual feedback which merely indicated that a button press was registered but not whether the response was correct or not. In a minority of trials, and thus unexpectedly, the feedback was omitted, or delayed by 500 ms. The results reveal a response hierarchy of activation strength in the dorsal striatum and the substantia nigra: the response to the delayed feedback was larger compared to immediate feedback and immediate feedback showed a larger activation compared to the omission of feedback. This suggests that brain regions typically involved in reward processing are also activated by non-rewarding, registering feedback. Furthermore, the comparison with immediate feedback revealed that both omitted and delayed feedback significantly modulated activity in a network of brain regions that reflects attentional demand and adjustments in cognitive and action control, i.e. the posterior medial frontal cortex, right dorsolateral prefrontal cortex, bilateral anterior insula, inferior frontal gyrus and inferior parietal lobe. This finding emphasizes the importance of immediate feedback in human-computer interaction, as the effects of delayed feedback on brain activity in the described network seem to be similar to that of omitted feedback.